Fusion Transcripts That Characterize Malignancies of Salivary Gland Origin. Issue 1 (January 2015) - García, Joaquín J.; Oliveira, Andre M.
<x xml:space="preserve">Abstract</x> Abstract Salivary gland neoplasia is often considered one of the more challenging areas of diagnostic surgical pathology. Given the overall rarity of salivary gland tumors, most surgical pathologists encounter them infrequently in practice. Naturally, this creates a risk for misclassification and inappropriate treatment. Challenges in salivary gland pathology are rooted in the dramatic histomorphologic overlap within between benign and malignant tumors. Although our understanding of the morphologic and immunophenotypic nuances of salivary gland neoplasia has improved over the years, even expert head and neck pathologists continue to struggle with a subset of cases using conventional surgical pathology techniques (morphology, histochemistry, and immunohistochemistry). Similarly, our understanding of salivary gland pathogenesis was historically based on morphologic and immunophenotypic observations rather than the molecular events that precede them. In recent decades, however, we have seen the unveiling of disease-defining fusion transcripts that encode novel oncoproteins or ectopically expressed normal or truncated oncoproteins in several salivary gland tumors. These fusion oncogenes typically encode transcriptional coactivators, transcription factors, and tyrosine kinases. Naturally, this offers significant promise with respect to diagnostic, prognostic, and predictive utility in the future. This review discusses fourmalignancies of salivary gland origin characterized by recurrent fusion gene events: mucoepidermoid carcinoma (CRTC1-MAML2), mammary analogue secretory carcinoma of salivary glands (ETV6-NTRK3), adenoid cystic carcinoma (MYB-NFIB), and hyalinizing clear cell carcinoma (EWSR1-ATF1).